Assemblages of deep-sea fishes on the middle slope off Northwest Africa (26°–33° N, eastern Atlantic). (December 2016) - Pajuelo, J.G.; Seoane, J.; Biscoito, M.; Freitas, M.; González, J.A.
Abstract: The structure and composition of deep-sea fish assemblages living on the middle slope off NW Africa (26–33° N) were investigated. Data were collected by six commercial trawlers during experimental fishing (1027 hauls) at depths between 800 and 1515 m. A total of 1, 115, 727 fish specimens, belonging to 37 families and 96 species (24 Elasmobranchii, 5 Holocephali, and 67 Actinopteri) were collected with bottom trawls. The deep-sea demersal fish fauna off NW Africa is dominated by fishes of the family Macrouridae, followed by the Moridae and Alepocephalidae families. The main abundant species were Trachyrincus scabrus, Bathygadus favosus, Mora moro, Alepocephalus productus, Nezumia aequalis and Bathygadus melanobranchus. PERMANOVA analysis showed differences in demersal ﬁsh assemblages among bottom types, depth strata and between areas (north and south of parallel 30° N), with the area being the most inﬂuential factor followed by the type of substrate. PERMANOVAs computed separately for each area showed signiﬁcant differences among the bottom types and depths in both areas. SIMPER analysis revealed that B. melanobranchus and B. favosus, which occurred at higher abundances in the area ≥30° N, were the species that were best discriminated between areas; whilst T. scabrus and M. moro occurred at higher abundances in the area <30° N. N. aequalis, B. favosus, B. melanobranchus, Deania hystricosa, Aphanopus intermedius, Coelorinchus labiatus and Halosaurus johnsonianus were restricted or more abundant in the area ≥30° N, and functioned as the discriminating species that most contributed to the average dissimilarity between areas. T. scabrus, M. moro, Alepocephalus productus and Alepocephalus bairdii were more abundant in the area <30° N. The standardized mean abundance (in number of individuals/km 2 ) showed a decreasing pattern: i) with depth in both areas, north and south of parallel 30° N, and ii) with depth on each type of substrate, except on cold coral bottoms. Hydrolagus mirabilis, Gadomus dispar, Nettastoma melanurum, Halosaurus ovenii, Chimaera opalescens, A. productus, Hoplostethus mediterraneus, Apristurus laurussonii and Trachyscorpia cristulata echinata showed a deeper Center of Gravity at latitudes ≥30° N, with differences in depths from 299 to 110 m compared to the area at latitudes <30° N. T. scabrus, Anoplogaster cornuta, B. favosus, Centrophorus squamosus, B. melanobranchus and A. bairdii showed a similar depth Center of Gravity, with differences in depths lower than 21 m. Highlights: The deep-sea benthic fish fauna off NW Africa is dominated by fishes of the family Macrouridae. The greatest diversity by latitude was observed in latitudes higher than 30° N. The fish abundance showed a decreasing pattern with depth. Boundary observed at latitude 30° N is linked to the upwelling event and slope topography. Assemblages observed in each area are related with the type of substrate of the slope.